Optoacoustic lenses for lateral sub-optical resolution elasticity imaging - Mengting Yao; Rafael Fuentes-Domínguez; Salvatore La Cavera, III; Fernando Pérez-Cota; Richard J. Smith; Matt Clark (Photoacoustics)
In this paper, we demonstrate for the first time the focusing of gigahertz coherent phonon pulses propagating in water using picosecond ultrasonics and Brillouin light scattering. We achieve this by using planar Fresnel zone plate and concave lenses with different focal lengths. Pump light illuminating the optoacoustic lens generates a focusing acoustic field, and Brillouin scattered probe light allows the acoustic field to be continuously monitored over time. Agreement of the experiment with a numerical model suggests that we can generate a focused acoustic beam down to ∼250 nm. A clear focusing effect is observed experimentally as a modulation of the envelope of the time-resolved Brillouin scattering (TRBS) signal. These findings are a crucial step toward their application in high-resolution acoustic microscopy. This work experimentally demonstrates a method to narrow the lateral size of picosecond laser-generated phonon fields in an aqueous environment, making it well-suited for 3D imaging applications in biological systems using TRBS.